Identifikasi Tren Perubahan Suhu Udara di Kota Padang - Pratiwi Gholil Prasetiyani; Yendri Sudiar, Nofi; Akmam; Hamdi (Journal of Climate Change Society, 2025)
The study examines he trend of air temperature in Padang City over the last three decades as part of efforts to understand regional climate variability and the potential impact of increasing global temperature on Padang City. The average, minimum, and maximum temperature data from the Minangkabau Meteorological Station for the period 1991–2020 and the Teluk Bayur Maritim Station for the period 1994–2020 were analyzed using Sen’s Slope Test to determine trend values and the Mann-Kendall Test to assess significance. The analysis results show a significant upward trend in average and minimum temperatures at Minangkabau Station, and maximum temperatures at Taluk Bayur Station. Urban Heat Island and industrial activities are the main factors of this increasing trend. If this trend continues to increase in the years to come, future temperature increases will be more extreme.